2022
DOI: 10.3390/vaccines10101619
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic Acid and Salicylic Acid Inhibit SARS-CoV-2 Replication in Precision-Cut Lung Slices

Abstract: Aspirin, with its active compound acetylsalicylic acid (ASA), shows antiviral activity against rhino- and influenza viruses at high concentrations. We sought to investigate whether ASA and its metabolite salicylic acid (SA) inhibit SARS-CoV-2 since it might use similar pathways to influenza viruses. The compound-treated cells were infected with SARS-CoV-2. Viral replication was analysed by RTqPCR. The compounds suppressed SARS-CoV-2 replication in cell culture cells and a patient-near replication system using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…2 C and supplemental Table S3 ), yielding a host target–drug network. Interestingly, multiple drugs suggested in this network, including acetylsalicylic acid, copper, and artenimol, indeed have been shown to inhibit SARS-CoV-2 replications ( 47 , 48 , 49 ), supporting the instructive value of the present findings. Moreover, our findings suggest that the N–host factor interaction could be a target of these anti-SARS-CoV-2 agents.…”
Section: Resultssupporting
confidence: 81%
“…2 C and supplemental Table S3 ), yielding a host target–drug network. Interestingly, multiple drugs suggested in this network, including acetylsalicylic acid, copper, and artenimol, indeed have been shown to inhibit SARS-CoV-2 replications ( 47 , 48 , 49 ), supporting the instructive value of the present findings. Moreover, our findings suggest that the N–host factor interaction could be a target of these anti-SARS-CoV-2 agents.…”
Section: Resultssupporting
confidence: 81%
“…Vero and Huh-7 cells were incubated with the compounds, and the cell growth rate was compared to untreated cells. In addition, we performed viability assays using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) on these cell lines and Calu-3 cells, as described previously [ 14 , 15 , 16 , 17 ]. Concentrations reducing cell growth or catabolism by 15% or more were excluded from further analyses ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the inhibition of viral replication by the protease inhibitors was analysed. The cells were incubated with the compounds and subsequently infected with SARS-CoV-2 at a multiplicity of infection (MOI) of 1 and incubated for three days, as described before [ 14 , 15 , 17 ]. Viral stocks contain non-infectious viruses that remain in the supernatant and influence the quantification of the viral genome.…”
Section: Resultsmentioning
confidence: 99%
“…It exhibited inhibitory properties against SARS-CoV-2 in silico (Jamhour et al 2022 ) β-sitosterol β-sitosterol showed inhibitory properties against SARS-CoV-2 in silico (Khan and Siddiqui 2020 ) Myristic acid Myristic acid and its derivatives exhibited inhibitory properties against human immunodeficiency virus and hepatitis B virus in vitro (Parang et al 1997 ) Pentadecylic acid Pentadecylic acid showed antioxidant, anti-inflammatory and anticancer properties (Sharma et al 2014 ) Ferulic acid Ferulic acid showed inhibitory properties against SARS-CoV-2 in silico (Bhowmik et al 2020 ) Sinapinic acid Sinapinic acid showed anti SARS-CoV-2 activity in vitro using Vero-E6 and in silico (Orfali et al 2021 ) Caffeic acid Caffeic acid showed anti-hepatitis C property (Erdemli et al 2015 ) p-coumaric acid The p-coumaric acid prolonged survival rates and reduced virus titers in bronchoalveolar lavage (BAL) fluids in mice model and showed anti-influenza activities (Pei et al 2016 ) Vanillic acid Vanillic acid showed neuroprotective properties. Treatment with vanillic acid for 14 consecutive days in animal model (Bilateral Common Carotid Artery Occlusion and Reperfusion) restored with the spatial memory (Sharma et al 2020 ) Salicylic acid Salicylic acid inhibited the SARS-CoV-2 activity in vero, Huh-7, and A549-ACE2 cell lines and in precision-cut, patient-derived lung slices (Geiger et al 2022 ) Cinnamic acid Cinnamic acid showed inhibitory properties against Zika virus infection in vitro in Vero cells, Huh7 cells and A549 cells It successfully blocked the RNA-dependent RNA Polymerase activity. Cinnamic acid reduced the mortality in Zika virus infected type I/II interferon receptor-deficient (ifnagr–/–) C57BL/6 (AG6) mice in vivo (Chen et al 2021 ) Albaspidin AA Albaspidin AA exhibited inhibitory activities against neuraminidase of Influenza virus (Xie et al 2023 ) Quinic acid Quin...…”
Section: Resultsmentioning
confidence: 99%